2014
DOI: 10.1002/jmri.24558
|View full text |Cite
|
Sign up to set email alerts
|

Noncontrast mapping of arterial delay and functional connectivity using resting‐state functional MRI: A study in Moyamoya patients

Abstract: Purpose To investigate if delays in resting-state spontaneous fluctuations of the BOLD (sfBOLD) signal can be used to create maps similar to time-to-maximum of the residue function (Tmax) in Moyamoya patients and to determine whether sfBOLD delays affect the results of brain connectivity mapping. Methods Ten patients were scanned at 3T using a gradient-echo EPI sequence for sfBOLD imaging. Cross correlation analysis was performed between each brain voxel signal and a reference signal comprised of either the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 26 publications
5
115
0
Order By: Relevance
“…In DSC-MRI, this is analogous to Tmax, which is the time taken for the contrast bolus to pass from the vessel from which the arterial input function is measured to the tissue. 18 Indeed, several studies 5,10 have shown a close relationship between Tmax and BOLD delay. MTT, however, predominantly reflects microvascular perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In DSC-MRI, this is analogous to Tmax, which is the time taken for the contrast bolus to pass from the vessel from which the arterial input function is measured to the tissue. 18 Indeed, several studies 5,10 have shown a close relationship between Tmax and BOLD delay. MTT, however, predominantly reflects microvascular perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of hemodynamic lag have used various reference signals including the whole brain signal, 9,10 homotopic regions, 26 and superior sagittal sinus. 27 We additionally measured lags between homotopic regions and found that lag laterality measured with a global gray matter references was correlated to lag laterality measured with homotopic reference (r ¼ 0.55, P < 10 À9 ). The gray matter tissue compartment defines a time series representing the hemodynamic response to neural activity averaged over the whole brain.…”
Section: Discussionmentioning
confidence: 99%
“…Mean arterial transit time can be thought of as the static component of cerebral perfusion while the HDR represents responses to neural activity. Therefore, a previously reported association between hemodynamic lag and mean arterial transit time 10,27 could suggest that lag is attributable to static blood flow changes. However, static changes alone do not account for hemodynamic lag of the presently observed large magnitudes (>2 s) because changes in transit time typically are on the order of less than 1 s. 36 Altered neural activity theoretically could contribute to observed hemodynamic lags.…”
Section: Physiological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was chosen as an additional measure because the global rs-fMRI signal has been linked to respiratory and cardiovascular fluctuations (Christen et al, 2015). Moreover, Liu et al (Liu et al, 2015) recently demonstrated strong associations between the global-signal correlation and CVR.…”
mentioning
confidence: 99%